Genocide and resistance Nr. 34(2) - Pocius, Mindaugas; Bagušauskas , Juozapas Romualdas; Grybkauskas, Saulius; Kareniauskaitė, Monika; Banionis, Juozas; Ražinskaitė, Ugnė (Genocidas ir rezistencija, 2013)
Fill Issue